Immunosuppressive role of CD11b+CD33+HLA‐DR− myeloid‐derived suppressor cells‐like blast subpopulation in acute myeloid leukemia - Shin Young Hyun; Eun Jung Na; Ji Eun Jang; Haerim Chung; Soo Jeong Kim; Jin Seok Kim; Jee Hyun Kong; Kwang Yong Shim; Jong In Lee; Yoo Hong Min; June‐Won Cheong (Cancer Medicine)
Abstract Objective Myeloid‐derived suppressor cells (MDSCs) facilitate tumor growth and development by suppressing T cell function; however, their role in acute myeloid leukemia (AML) remains unclear. Here, we investigated the immunosuppressive role and prognostic value of blasts with an MDSC‐like phenotype. Methods CD11b+CD33+HLA‐DR− MDSC‐like blasts from bone marrow mononuclear cells of patients with AML were analyzed. To investigate their T cell‐suppressing function, MDSC‐like blasts were isolated using flow cytometry and co‐cultured with CD8+ cytotoxic T cells and NB4 leukemic cells. Treatment outcomes were then compared between the MDSC‐like blasts low (≤9.76%) and high (>9.76%) groups to identify clinical significance. Results MDSC‐like blasts showed higher expression of arginase‐1 and inducible nitric oxide synthase. Isolated MDSC‐like blasts significantly suppressed CD8+ T cell proliferation induced by phytohemagglutinin A. NB4 cell proliferation was significantly suppressed upon co‐culture with CD8+ cytotoxic T cells and partially restored upon co‐culture with MDSC‐like blasts. Patients with high MDSC‐like blasts at diagnosis showed substantially shorter overall survival and leukemia‐free survival relative to low MDSC‐like blasts patients, with subgroup analysis showing statistically significant differences in patients not receiving allogeneic hematopoietic stem cell transplantation. Conclusion We demonstrated that MDSC‐like blasts drive AML‐specific immune‐escape mechanisms by suppressing T cell proliferation and restoring T cell‐suppressed NB4 cell proliferation, with clinically higher fractions of MDSC‐like blasts at diagnosis resulting in poor prognosis.